Mechanical and dielectric properties of polyimide/silica nanocomposite films. (December 2015) - Cui, X.; Zhu, G.; Liu, W.; Wang, K.; Ren, F.; Fu, H.; Yan, X.
Abstract : Polyimide/silica (PI/silica) nanocomposite films were successfully prepared via in situ dispersive polymerisation and thermal imidisation. In order to obtain homogeneous nanoscale dispersibility and good compatibility with the PI matrix, hydrophobic aerosil was selected as the nanosilica precursor. 4, 4-Bis(3-aminophenoxy)biphenyl (4, 3-BAPOBP) was used as diamine to improve the processability of PI. The PI/silica nanocomposite films were characterised using Fourier transform infrared spectroscopy, scanning electron microscopy and differential scanning calorimetry. The mechanical and dielectric properties of the films were also measured. The results demonstrate that the tensile strength and breakdown strength of films can be markedly improved by the addition of appropriate amounts of silica to the PI matrix. At a silica content of 4.0 wt-%, the tensile strength and the breakdown strength of the films increased by 21 and 13%, respectively, compared with the neat PI. Thus, it is feasible to use nanosilica to improve the properties of PI.